The two towers : - Tolkien, J. R. R. (Houghton Mifflin, 1994)
The magnificence of Rob Inglis' dramatization, both with respect to its place in the Tolkien Legend and in comparision to the present state of the spoken theatre, is quite simply ineffible. Here presented is THE ONLY completely unabriged reading of the Lord of the Rings to be found, and to commuters like me, it represents a long awaited opportunity to become aquianted with the work of a genius without fear of losing precious shards of his masterpiece to the whim of an editor. Worth every moment of the 20 hour listening time, from the endearing character voices to the hearty singing of songs and chanting of poetry that is sure to linger in your mind throughout the day. A purely wonderful experience for both Tolkien Veterans and the uninitiated alike.